2019
DOI: 10.3390/ijms20081820
|View full text |Cite
|
Sign up to set email alerts
|

BNP and NT-proBNP as Diagnostic Biomarkers for Cardiac Dysfunction in Both Clinical and Forensic Medicine

Abstract: Currently, brain natriuretic peptide (BNP) and N-terminal proBNP (NT-proBNP) are widely used as diagnostic biomarkers for heart failure (HF) and cardiac dysfunction in clinical medicine. They are also used as postmortem biomarkers reflecting cardiac function of the deceased before death in forensic medicine. Several previous studies have reviewed BNP and NT-proBNP in clinical medicine, however, few articles have reviewed their application in forensic medicine. The present article reviews the biological feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
181
1
29

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(216 citation statements)
references
References 127 publications
5
181
1
29
Order By: Relevance
“…Previous forensic studies reported that the concentrations of biomarkers in the pericardial fluid, which is close to the heart, were higher than those in the peripheral bodily fluids . In addition, the pericardial fluid is present in the enclosed space between the pericardium and the heart and cannot be easily influenced by postmortem changes such as hemolysis . The present meta‐analysis showed that NT‐proBNP in pericardial fluid, rather than in serum, revealed statistical elevation, which indicated that pericardial fluid might outperform serum in postmortem biochemical analysis.…”
Section: Discussionmentioning
confidence: 51%
“…Previous forensic studies reported that the concentrations of biomarkers in the pericardial fluid, which is close to the heart, were higher than those in the peripheral bodily fluids . In addition, the pericardial fluid is present in the enclosed space between the pericardium and the heart and cannot be easily influenced by postmortem changes such as hemolysis . The present meta‐analysis showed that NT‐proBNP in pericardial fluid, rather than in serum, revealed statistical elevation, which indicated that pericardial fluid might outperform serum in postmortem biochemical analysis.…”
Section: Discussionmentioning
confidence: 51%
“…But their usefulness for diagnosis of SCD is arguable (1). The synthesis of BNP is induced by mechanical stress, ischemia and hypoxia; which result in BNP rise in the myocardium (49). In support of this, animal studies (50) demonstrated that BNP mRNA in left ventricle of rats is influenced by Angiotensin II, stimulated by mechanical stress.…”
Section: Brain Natriuretic Peptide (Bnp)mentioning
confidence: 89%
“…The covariates included were age, systolic blood pressure on admission, diastolic blood pressure on admission, Killip class on admission, heart rate on admission, culprit coronary artery, number of arteries with sign cant stenosis (de ned as > 70%), SYNTAX score, pain to baloon time, diabetes, weight, BMI, dyslipidaemia, smoking status, previous medical therapy, medical therapy on dismissal, hypertension, prior cerebrovascular disease, CK value at admission, 6 The aim of this model was to nd out which independent variables are independently related to the dependent variable, and the same was used in all forms of regression. ESVi was used as a dependent variable in the multivariate analysis, and a maximum of 6 variables were used in each model, which is appropriate to the sample size.…”
Section: Methodsmentioning
confidence: 99%
“…It is released to the bloodstream by myocytes undergoing wall tension due to volumetric or pressure overload. (5) It is well known that acute ischemic heart disease is associated with an elevation of BNP levels, which might re ect the severity of LV dysfunction (6). NTproBNP together with systolic blood pressure on admission could represent the Killip classi cation system, which is using physical examination and the development of heart failure in order to predict and stratify the risk of mortality after an acute myocardial infarction.…”
Section: Roc Analysis Found Great Predictive Value Of the Nomogrammentioning
confidence: 99%